2021
DOI: 10.1002/jmv.27280
|View full text |Cite
|
Sign up to set email alerts
|

Elevated inflammatory markers are associated with poor outcomes in COVID‐19 patients treated with remdesivir

Abstract: The antiviral remdesivir has been shown to decrease the length of hospital stay in coronavirus disease 2019 (COVID‐19) patients requiring supplemental oxygen. However many patients decompensate despite being treated with remdesivir. To identify potential prognostic factors in remdesivir‐treated patients, we performed a retrospective cohort study of patients hospitalized at NewYork‐Presbyterian Hospital/Weill Cornell Medical Center between March 23, 2020 and May 27, 2020. We identified 55 patients who were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
4
8
0
Order By: Relevance
“…13 Recent reports have shown that some patients with the severe form of the Covid-19 infection experience an intensified immune response similar to cytokine release syndrome and multisystem inflammatory syndrome. 14 Consistent with us, a prior study by Stoeckle et al 15 have shown that CRP levels decrease significantly after remdesivir therapy in none intubated Covid-19 patients, indicating that remdesivir mitigates inflammatory response in a certain group of patients but not in all. Moreover, women patients in the study had lower CRP levels than men that may be due to the lower viral load level, higher number of CD 4+ T cells, and higher levels of antibodies in women.…”
Section: Discussionsupporting
confidence: 84%
“…13 Recent reports have shown that some patients with the severe form of the Covid-19 infection experience an intensified immune response similar to cytokine release syndrome and multisystem inflammatory syndrome. 14 Consistent with us, a prior study by Stoeckle et al 15 have shown that CRP levels decrease significantly after remdesivir therapy in none intubated Covid-19 patients, indicating that remdesivir mitigates inflammatory response in a certain group of patients but not in all. Moreover, women patients in the study had lower CRP levels than men that may be due to the lower viral load level, higher number of CD 4+ T cells, and higher levels of antibodies in women.…”
Section: Discussionsupporting
confidence: 84%
“…Signi cant reduction in CRP levels and in ammatory cytokines levels were seen in remdesivir treated group patients indicating the immunomodulatory and anti-in ammatory role of remdesivir as well as corticosteroids therapy [25][26]. Also, these ndings are consistent with the study by Kate Stoeckle et al which shows CRP levels decreased signi cantly after remdesivir administration in patients who remained non-intubated over the study period [27]. The decrease in CRP levels after corticosteroids administration has also been well documented in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Some authors demonstrated that systemic inflammation can modify drug plasma metabolism. 23 , 24 Therefore, the inflammatory profile related to SARS-CoV-2 infection could influence the remdesivir PK in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%